Reflective processes in clinical simulations from the perspective of the simulation actors. Issue 6 (2nd November 2022) - Levin, Orna
ABSTRACT: Simulation-based learning (SBL) relies on reflective practices presented from the perspectives of the participants, instructors, and actors. To date, most research in SBL has examined the reflectivity of the simulation participants and simulation instructors; only a few have considered the professional actors' perspectives, and these did not explore their reflective activity in depth. This study is the first attempt to focus specifically on the reflective practices of the professional simulation actors in the SBL process. Fifteen professional simulation actors participated in this case study. Triangulation was achieved by using three data collection tools: reflections, interviews, and focus groups. An inductive analysis of the data revealed the professional actors' efforts to establish a reflexive relationship with the simulation participants and its significance in the SBL process. The adoption of the clinical model, originating from the medical field, in the field of teacher education, as well as the study's focus on the practice of reflectivity rather than on specific content, suggests that the findings regarding the simulation actors' reflective processes may be applied to other fields.